Synergistic effects of notoginsenoside R1 and saikosaponin B2 in atherosclerosis: A novel approach targeting PI3K/AKT/mTOR pathway and macrophage autophagy - Yihua Wang; Qing Liao; Xue Mei; Han Xu; Lijun Luo; Rong Huang; Yue Tang; Chunyang Zhou (PLoS ONE, 2025)
Atherosclerosis (AS) is a major global contributor to cardiovascular diseases and associated mortality. The traditional treatment primarily relies on statins; however, these drugs are often linked to side effects such as liver dysfunction and muscle impairment. Recent studies have highlighted the potential protective properties of saponin compounds derived from traditional herbal sources, such as notoginsenoside R1 (NGR1) and saikosaponin B2 (SSB2), in combating atherosclerosis. However, the comprehensive effects of these compounds against atherosclerosis and their underlying mechanisms remain inadequately understood. Firstly, we employed network pharmacology analysis to identify 113 common targets, including mTOR and CASP3, for NGR1, SSB2, and atherosclerosis from databases such as TCMSP. We constructed a protein-protein interaction (PPI) network and performed GO and KEGG enrichment analyses, whcih revealed key signaling pathways involved in PI3K/Akt, inflammation, and autophagy. The atherosclerosis model was established using ApoE-/- mice fed with a “Western diet” followed by treatment with NGR1, SSB2, or NS combination. Histological examinations, including hematoxylin-eosin (HE) staining, oil red O (ORO) staining, and CD68 immunofluorescence, were conducted to evaluate the pathological conditions of the aortic root, liver and kidneys in ApoE-/- mice. Our findings demonstrate that the NS combination improves lipid levels, lipid transport, and unstable plaque formation in ApoE-/- mice without adverse effects on liver or kidney function. Finally, oxidized low-density lipoprotein (ox-LDL) was used to culture RAW264.7 macrophages to establish an in vitro foam cell model. The effects of NS combination on lipid uptake, inflammatory response, apoptosis, the PI3K/Akt/mTOR signaling pathway, and autophagy were evaluated using methods such as CCK-8 assay, Oil Red O staining, immunofluorescence analysis, flow cytometry, RT-PCR, and Western blot analysis. The results indicated that NS combination promoted autophagy by inhibiting the PI3K/Akt/mTOR pathway. This significantly alleviated inflammation, reduced apoptosis, and decreasing lipid accumulation, thereby improving the pathological progression of atherosclerosis. Collectively, this study demonstrates, for the first time, that the NS combination synergistically activates macrophage autophagy by suppressing the PI3K/AKT/mTOR pathway, thereby attenuating lipid accumulation, inflammation, and apoptosis in atherosclerotic models.